Power, policies, and algorithms - technologies of surveillance in the European border surveillance regime - Huber, Georg Johannes (KIT Scientific Publishing, 2022)
This work analyses the emergent European border surveillance regime as part of the European border regime/migratory regime and the power structures this technologogical regime is embedded into, is reproducing and creating. The history, politics, policies and technological characteristics of the border surveillance regime of the EU are analysed through a theoretical framework based in political science, political sociology and surveillance studies.